1969
DOI: 10.3758/bf03210534
|View full text |Cite
|
Sign up to set email alerts
|

Tests of product and additive scaling axioms

Abstract: For convenience in testing, the product axiom may be written in its logarithmic form:A special feature of these axioms is that they are applied before any scale is constructed, and a subset of the data is used to predict the residual data. Tests based on scales constructed from all the data are more likely to obscure possible violations ApparatusThe apparatus, described in detail elsewhere (Eskildsen, 1963), provided four luminous white circular targets 13 mm in diam, placed horizontally and separated by 90 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…These results agree with Torgerson's conjecture and Fagot and Stewart's (1969) consistency tests. They suggest that the reason why ratio evaluation and difference evaluation are based on a single judgment operation is that participants use the difference operation for both evaluations.…”
Section: Reality Of Difference Evaluationsupporting
confidence: 83%
See 2 more Smart Citations
“…These results agree with Torgerson's conjecture and Fagot and Stewart's (1969) consistency tests. They suggest that the reason why ratio evaluation and difference evaluation are based on a single judgment operation is that participants use the difference operation for both evaluations.…”
Section: Reality Of Difference Evaluationsupporting
confidence: 83%
“…It turned out that Ρ AC ≠ Ρ AB ⋅ Ρ BC and Δ AC 0 Δ AB + Δ BC . If Torgerson's hypothesis that people cannot distinguish ratios from differences holds, then Fagot and Stewart's (1969) results suggest that people are able only to evaluate sensory differences.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…IRECT HlsK sClUND PRESSURE !DYNES/50 eM) (Fagot & Stewart,1%9). What has emerged from these studies is that (1) inverse attribute scales tend to be reciprocals of their counterpart scales, but that some evidence suggests they are not perfect reciprocals; (2) multiple and fractional judgments are nearly reciprocally related for group data and for some individuals, but that many individuals do not show reciprocal asymmetry; and (3) multiplicative transitivity does not usually hold for group or individual subject data (Fagot & Stewart, 1969). Inverse cross-modality matching provides a different technique for the assessment of consistency.…”
Section: Individual Differences In Exponentsmentioning
confidence: 99%
“…Since v 1 v 2 v 3 , the equality n 1 n 2 n 3 occurs when n i v i (where i 1, 2, or 3). Fagot and Stewart (1969) found that n 1 n 2 n 3 . Consequently, n i v i .…”
Section: Testmentioning
confidence: 99%